The effect of uncertainty on investment: Evidence from EU survey data - Atanas Kolev; Timothy Randall (European Investment Bank (EIB), 2024)
Using firm-level survey data combined with firm-level financial information, we investigate the effect of a subjective, firm-specific measure of uncertainty on firm investment and employment growth in the European Union. We find that uncertainty has an economically significant negative effect on investment. Uncertainty is found to have an economically significant negative effect on employment growth, as well. Firms perceiving uncertainty as a major investment impediment experience 1 p.p. lower employment growth compared to those that do not. Using our estimates, we find that non-financial corporate investment in the European Union in 2022 would have been higher by 1 p.p. of fixed assets, while employment growth would have been by 0.7 p.p. higher had uncertainty remained at its 2021 levels.
Keywords: D22; D84; G31; 330